Pilot-scale production of xylo-oligosaccharides and fermentable sugars from Miscanthus using steam explosion pretreatment. (January 2020) - Bhatia, Rakesh; Winters, Ana; Bryant, David N.; Bosch, Maurice; Clifton-Brown, John; Leak, David; Gallagher, Joe
Graphical abstract: Highlights: ~50 % (w/w) of initial xylan in biomass recovered as XOS in the liquid fraction. Xylobiose yields of up to 500 g/kg of initial xylan using commercial enzymes. ~75 % conversion of initial xylan in biomass to XOS. Up to 70 % hydrolysis of glucan from residual solids to fermentable glucose. Abstract: This study investigated pilot-scale production of xylo-oligosaccharides (XOS) and fermentable sugars from Miscanthus using steam explosion (SE) pretreatment. SE conditions (200 °C; 15 bar; 10 min) led to XOS yields up to 52 % (w/w of initial xylan) in the hydrolysate. Liquid chromatography-mass spectrometry demonstrated that the solubilised XOS contained bound acetyl- and hydroxycinnamate residues, physicochemical properties known for high prebiotic effects and anti-oxidant activity in nutraceutical foods. Enzymatic hydrolysis of XOS-rich hydrolysate with commercial endo -xylanases resulted in xylobiose yields of 380 to 500 g/kg of initial xylan in the biomass after only 4 h, equivalent to ~74 to 90 % conversion of XOS into xylobiose. Fermentable glucose yields from enzymatic hydrolysis of solid residues were 8 to 9-fold higher than for untreated material. In view of an integrated biorefinery, we demonstrate the potential for efficient utilisation of Miscanthus for the production of renewable sources, including biochemicals and biofuels.